CONTINENTAL GROWTH IN THE PROTEROZOIC: A GLOBAL PERSPECTIVE - Windley B.F. (My University, 2003)
During Proterozoic time, growth of the continents took place by the addition of mantlederived, juvenile material to pre-existing continental blocks. This accretion took place largely within three tectonic environments: (1) most importantly, in accretionary orogens such as the Birimian, the Baltic Shield, the Arabian-Nubian Shield and the early Altaids in Central Asia-these orogens grew largely by the accretion of island arcs, oceanic plateaus, accretionary prisms and ophiolites; (2) in the juvenile parts of collisional orogens as in the Trans-Hudson and Grenville; (3) within supercontinents that underwent rifting and breakup, giving rise to continental flood basalts and mafic dyke swarms. In addition to plate tectonics, the role of plume tectonics is increasingly emphasized as a fundamental process in Earth evolution. A mantle superplume may increase the oceanic spreading rate, the subduction rate and thus the island-arc production rate. It may also be responsible for the formation of a supercontinent, thus preserving the juvenile parts of collisional orogens, and it may be instrumental in the fragmentation of a supercontinent, giving rise to juvenile continental flood basalts. The balance between these processes is still poorly understood, as are calculated growth rates of Proterozoic crust.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой